Seed germination of the invasive species Piper aduncum as influenced by high temperature and water stress. (29th January 2015) - Wen, B; Xue, P; Zhang, N; Yan, Q; Ji, M; Batlla, Diego
Summary Piper aduncum is a common woody weed throughout the tropics and a successful invader in many areas. As this species most often dominates roadsides and forest margins, and these habitats frequently experience extreme changes in temperature and water availability, it is important to understand how the seeds adapt to these stresses. This study investigated the effect of high temperatures and water stress, continuous, periodic or transient, on P. aduncum seed germination before or after imbibition. It was found that P. aduncum seeds exhibited only intermediate tolerance and did not germinate at temperatures above 35°C or water potentials below −0.6 MPa. However, this species is well adapted to local conditions, with fruit ripening in the rainy season, seed desiccation tolerance to eRH 8%, rapid germination under wet conditions, higher temperature tolerance than the maximum ground temperature, germination of most seeds after 60 h continuous heat treatment or daily periodic heat treatments up to 5 h at 40°C and insensitivity to 12 h heat treatment at 40°C during the whole germination process. The intermediate tolerance to high temperature and water stress of P. aduncum, in combination with local environmental conditions in Xishuangbanna, makes P. aduncum an intermediate invader in this area.